Aromatase inhibitors: The unexpected breast cancer treatment. Issue 3 (April 2020) - Pieters, Huibrie C.; Green, Emily; Sleven, Miriam; Stanton, Annette L.
Abstract: Objective: Suboptimal adherence with endocrine treatment for breast cancer is influenced by a number of factors but remains poorly understood. We sought to describe the prior knowledge about and expectations of breast cancer treatments among older women retrospecting on their diagnosis and treatment. Methods: Thematic analysis was used to systematically analyze data obtained with face-to-face, open-ended interviews conducted with 54 women who had filled at least one prescription for an aromatase inhibitor. The average age was 71.9 (65–93) years at diagnosis. Results: Three salient themes were described: the sources of information on which preknowledge and expectations surrounding treatment were founded, and two phases of treatment, primary (surgery, chemotherapy and radiation therapy) and anti-hormonal. The main source of information was from family and friends who had been treated for cancer. These peers reported both positive and negative experiences and in many cases contributed to the women having some degree of misinformation. A foundational knowledge of primary treatments was evident (necessity, duration, intensity, side-effects) and that receiving one or more treatments was needed. Compared to primary treatments, anti-hormonal treatment (AHT) was unexpected, the women knew less about it, and felt comparatively under-prepared for this treatment. Conclusions: The transition from primary treatments to adjuvant AHT therapy with receiving a prescription for an aromatase inhibitor caught many participants off guard. Our findings elucidate areas to enhance clinical practice, expand the research agenda to more thoroughly explore AHT information and design of an age-appropriate supportive intervention to improve continuation with AHT.